Financial insights from the last few components of a stock market PCA - Libin Yang; William Rea; Alethea Rea (International Journal of Financial Studies, 2017)
We show that the last few components in the principal component analysis of the correlation matrix of a group of stocks may contain useful financial insights by identifying highly correlated pairs or larger groups of stocks. The results of this type of analysis can easily be included in the information an investor uses to manage an investment portfolio.
Keywords: G11; 330; principal component analysis; stock correlation; diversification; stock portfolios; ASX 200